Intra-Articular Entrapment of the Medial Epicondyle following a Traumatic Fracture Dislocation of the Elbow in an Adult - Hicham G. Abdel Nour; George S. El Rassi; Jack C. Daoud; Youssef G. Hassan; Rami A. Ayoubi; Nabih I. Joukhadar (Case Reports in Orthopedics)
Medial epicondyle entrapment after an acute fracture dislocation of the elbow is a common finding in the pediatric population, but a rare finding in adults. We present a case of an adult patient diagnosed with a traumatic fracture dislocation of the elbow joint with intra-articular entrapment of the medial epicondyle. After initial evaluation, closed reduction was done. Stability testing after reduction showed an unstable joint; thus, open reduction and internal fixation was decided.